Peranan Intention To Act Sebagai Mediator Antara Big-Five Personality Dengan Responsible Environmental Behavior Peserta Didik SMA Negeri Di Jakarta - Rena Rahmani (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
Environmental problems have continued to increase since the last 3 years, mostly caused by human activities. It is important to understand the factors of students as the next generation whether they carry out responsible environmental behavior. This study aims to determine the effect of intention to act on the environment as a mediator between the big-five personality and the responsible environmental behavior of students. The sample for this research was 100 students at SMAN 6 Jakarta in the odd semester of the 2022/2023 school year. The method used is a survey method through causal studies and analyzed by path analysis. The research instruments used were responsible environmental behavior (22 items, reliability 0.893), big-five personality (26 items, reliability 0.877), and intention to act (25 items, reliability 0.918). The results showed big-five personality has a direct influence on the intention to act on the environment significantly, intention to act on the environment has a direct effect on responsible environmental behavior significantly, big-five personality has a direct influence on responsible environmental behavior significantly, and and the results of intention to act are suitable as mediating variables between personality and responsible environmental behavior on students. Keywords: Big-Five Personality, Intention to Act, Path Analysis, Responsible Environmental Behavior.